PERANCANGAN PHYSICS PUZZLE GAME “INSERT THE BALL!” PADA PLATFORM ANDROID - Robby Setiawan; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
"Insert The Ball!" is a Physics Puzzle Game for Android Platform. Physics Puzzle Game is type of puzzle game where the player must use physics to complete the game. In This Game player must put the ball inside the ring. Player can draw objects and cut objects to aim  the ball into the ring.